Acquiring Potential Blood Donors in Large Cities: A Preference-Based Donor Segmentation Study. Issue 4 (1st October 2016) - Boenigk, Silke; Leipnitz, Sigrun
ABSTRACT: In contrast to previous segmentation studies that apply mostly demographic segmentation criteria, this study presents a behavioral segmentation approach to explain how potential blood donors in large cities can be most effectively clustered and acquired. The authors conduct a representative online panel study among 2, 062 potential blood donors living in the four largest cities of Germany—Berlin, Hamburg, Munich, and Cologne. Applying explorative factor analysis and cluster analysis, the study identifies and describes seven preference-based blood donor segments. Using the segmentation results, the authors derive several blood donor acquisition strategies that are directly linked to the identified preferences.